2018
DOI: 10.2478/fman-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Employee’s Learning in the Organization - A Study of Knowledge Based Industries

Abstract: This paper focuses on reviewing the learning behavior of individual employees in the firm over other influencing factors in knowledge-based industries in Sri Lanka. Using a stratified random sampling technique, a sample of 143 employees from jobs in Database Administration & Development, Systems & Network Administration, Web Development & Programming and Software Engineering was selected as respondents for the survey from 13 knowledge based industrial firms in Sri Lanka. After a descriptive analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Bothma and Roodt (2013) defined turnover intention as "the final step in the decision-making process before a person actually leaves a workplace" (p. 2). Kuruppuge and Gregar (2018) also defined turnover intention as "the mental readiness of employees to leave the firm" (p. 16). Thereby, lowering the turnover intention of talented employees will result in a gain to organizational performance because when an employee's action changes from intending to leaving to actually leaving, it puts the organization in an unfavorable position by increasing costs related to recruiting and training, as well as lowering productivity level (George, 2015;Susilawati & Darma, 2019).…”
Section: Literature Review the Influence Of Olc On Turnover Intentionsmentioning
confidence: 99%
“…Bothma and Roodt (2013) defined turnover intention as "the final step in the decision-making process before a person actually leaves a workplace" (p. 2). Kuruppuge and Gregar (2018) also defined turnover intention as "the mental readiness of employees to leave the firm" (p. 16). Thereby, lowering the turnover intention of talented employees will result in a gain to organizational performance because when an employee's action changes from intending to leaving to actually leaving, it puts the organization in an unfavorable position by increasing costs related to recruiting and training, as well as lowering productivity level (George, 2015;Susilawati & Darma, 2019).…”
Section: Literature Review the Influence Of Olc On Turnover Intentionsmentioning
confidence: 99%
“…When people know that they will leave their job, they are less motivated to learn new things as it does not seem useful to them (Kuruppuge & Gregar, 2018). Furthermore, preliminary evidence from interviews with 20 employees, who were introduced to a new technology, indicated that time until retirement played a role in experiencing that technology as useful (Ouadahi, 2008).…”
Section: A Motivational Pathway Via Future Time Perspective and Perce...mentioning
confidence: 99%
“…However, in previous studies, employees’ learning behavior has usually been regarded as a relatively stable variable for an individual. Those studies found that many factors could affect employee learning behavior, such as organizational environment (O’Leary and Studer, 2001), employees’ organizational identification (Kuruppuge and Gregar, 2018) and knowledge sharing (Eid and Nuhu, 2011). However, ignoring the fact that employees’ learning behavior might vary within person across time could lead to missing out the complexity of human behavior.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%